Methodology to prioritize local food systems issues and identify possible demand-based actions and interventions in Viet Nam - CGIAR Research Program on Agriculture for Nutrition and Health (2021)
The methodology has been applied and the resulting food systems profiles were published and disseminated. They are designed to help researchers and policymakers understand the existing challenges among the elements of the food system and help develop actionable policy recommendations for local socioeconomic development.